Evaluation of inhibitory and lethal activity of lavender oil against two fungi Alternaria citri and Drechslera dematioidea (Latakia University Journal -Biological Sciences Series, 2022)
In this research was studied the effect of different concentrations of lavender oil on the growth of Alternaria citri and Drechslera dematioidea .All concentration revealed obvious inhibitor activity against both fungi the inhibitory effect differenced as difference of concentrate.The concentrations 0.06 – 0.04 – 0.03 – 0.02- 0.006 – 0.004 g/ml showed 100%inhibition against Drechslera dematioidea and the inhibition rate was 60%  at  0.002g/ml concentration on the eleventh day of incubationThe constrictions0.06 – 0.04 – 0.03 – 0.02- 0.006 – 0.004 – 0.002  g/ml showed  complete inhibition against the Alternaria citri and at constrictions 0.01g/ml the percentage of  inhibition  was 30.55%. The minimum bactericidal concentrations ( MBC) of lavender oil was 0.006g/ml agaist Drechslera dematioidea and it was 0.002g/ml against Alternaria citri .